A comparative study of head circumference and foot length as a measure of low birth weight in neonates - Rathod, Vaibhav B.; Mehkarkar, Nitin S.; Gode, Vaibhav K. (International Journal of Contemporary Pediatrics, 2023)
Background: Birth weight is the single most important indicator of survival, growth and overall development of the child. New-borns with less than 2.5 kg birth weight are termed as low birth weight (LBW). Approximately 28% babies in India are LBW. LBW is associated with high neonatal morbidity and mortality. Early diagnosis of LBW and apt intervention can lead to favourable outcome. The 70-80% of births take place either at home or at peripheral hospitals. Measuring birth weight is difficult in India due to resource limited set up. There is a need of alternative methods to detect LBW which should be simple, handy, quick and cost effective. Hence, we decided to do study of correlation of calf muscle circumference and chest circumference with birth weight to determine LBW in new-borns. Aim of the study was to study head circumference and foot length in diagnosing LBW babies. Objectives were to correlate above-said anthropometric parameters with birth weight and to decide indicator with better correlation with birth weight amongst head circumference and foot length Method: Its a cross sectional study conducted in tertiary care centre in North Maharashtra. The 162 new-borns (34- 42 weeks gestation) were included in Study. Birth weight, head circumference, and foot length were measured with appropriate scientific method. Results are analyzed with SPSS software and Microsoft excel. Results: Cut-off value to detect LBW is 31cm and 8.2 cm for head circumference and foot length respectively. Head circumference had better correlation (r=0.73) as compared to foot length (r=0.30). Head circumference has 87% sensitivity and 68% specificity as compare to foot length which has 74.8% sensitivity and 46.8% specificity respectively. Conclusions: Head circumference and foot length circumference can be used to determine LBW, though larger study with a greater number of patients is needed to establish precise correlation.